Experimental investigation into cyclic working performances of prefabricated CFST columns with improved column-footing connections. (1st April 2022) - Di, Jin; Han, Bin; Zhou, Xuhong; Hu, Long; Qi, Yong; Qin, Fengjiang
Abstract: Prefabricated concrete-filled steel tube (CFST) column systems with two types of column-footing connections were proposed. Eight circular prefabricated CFST columns with a diameter of 400 mm and a reinforced concrete column were investigated by applying the horizontal reciprocating loads. The investigation compared and analyzed the experimental phenomena, bearing capacity, ultimate drift angle, hysteresis curves, envelope curves, and dissipated energy of prefabricated CFST columns with different column-footing connections (bolt connection and embedded connection), steel tube thicknesses (2 mm, 6 mm, and 10 mm), axial compressive load levels (0.1, 0.2, 0.3) and opening plate configurations. The prefabricated CFST columns with bolt and embedded connections had similar bearing capacity, but the latter had superior ductility and energy consumption performance. The difference in bearing capacity between CFST columns with bolt and embedded connections was only 3.7%, but the ultimate drift angle and dissipated energy of the latter increased by 23.5% and 166.6%, respectively. The steel tube thickness and the axial compressive load level had significant effects on the mechanical properties of the prefabricated CFST columns. When the steel tube thickness increased from 2 mm to 6 mm, the bearing capacity, ultimate drift angle, and dissipated energy of the specimens increased by 64.6%, 34.2%, and 278.2%, respectively. When the axial compression ratio increased from 0.1 to 0.3, the bearing capacity, ultimate drift angle, and dissipated energy of the specimens increased by 18.0%, 43.2%, and 224.0%, respectively. Finally, the experimental bearing capacity of the prefabricated CFST columns was compared with that calculated by the design specification, and this comparison showed that the two column-footing connections can make the prefabricated CFST columns possess excellent integral mechanical properties. Highlights: Develop the prefabricated steel tube half-confined concrete columns. Justify the cyclic bearing capacity of embedded and bolt connections. Demonstrate the dissipating energy ability of embedded connections. Show the better ductility of embedded connections than bolt connections.